리튬 및 발프로에이트 병용 처치가 PC12 세포에서 ERK1/2 인산화와 ELK1 및 C-FOS 전사활성에 미치는 영향 - 차승근; 김세현; 하규섭; 신순영; 강웅구; Cha, Seung Keun; Kim, Se Hyun; Ha, Kyooseob; Shin, Soon Young; Kang, Ung Gu (Journal of the Korean Society of Biological Psychiatry, 2013)
Objectives Mechanisms of clinical synergistic effects, induced by co-treatments of lithium and valproate, are unclear. Extracellular signal-regulated kinase (ERK) has been suggested to play important roles in mechanisms of the action of mood stabilizers. In this study, effects of co-treatments of lithium and valproate on the ERK1/2 signal pathway and its down-stream transcription factors, ELK1 and C-FOS, were investigated in vitro. Methods PC12 cells, human pheochromocytoma cells, were treated with lithium chloride (30 mM), valproate (1 mM) or lithium chloride + valproate. The phosphorylation of ERK1/2 was analyzed with immunoblot analysis. Transcriptional activities of ELK1 and C-FOS were analyzed with reporter gene assay. Results Single treatment of lithium and valproate increased the phosphorylation of ERK and transcriptional activities of ELK1 and C-FOS, respectively. Combined treatments of lithium and valproate induced more robust increase in the phosphorylation of ERK1/2 and transcriptional activities of ELK1 and C-FOS, compared to those in response to single treatment of lithium or valproate. Conclusions Co-treatments of lithium and valproate induced synergistic increase in the phosphorylation of ERK1/2 and transcriptional activities of its down-stream transcription factors, ELK1 and C-FOS, compared to effects of single treatment. The findings might suggest potentiating effects of lithium and valproate augmentation treatment strategy.